2016
DOI: 10.1080/21642850.2016.1168301
|View full text |Cite
|
Sign up to set email alerts
|

Work-privacy conflict and musculoskeletal pain: a population-based test of a stress-sleep-mediation model

Abstract: Previous research has shown that work-privacy conflict (WPC) is associated with musculoskeletal pain (MSP), but the processes involved are unclear. This study simultaneously tested strain and sleep problems as mediators in three mediation paths (WPC →strain→MSP; WPC →sleep problems→MSP; and WPC →strain→sleep problems→MSP). Total mediation (including all three mediation paths) was expected to be stronger in older compared to younger participants, in participants doing shift work compared to those with regular w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The present study controlled for age (1 ≤ 20 years; 2 = 20–29 years; 3 = 30–39 years; 4 = 40–59 years, 5 = 60–65 years) and gender (0 = male; 1 = female) because past studies have shown that age and gender affect MSCs in employees (Baur et al 2018 ; Elfering et al 2016 ). To take individual requirements into account, this study also controlled for full- or part-time employment, as suggested by Elfering et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study controlled for age (1 ≤ 20 years; 2 = 20–29 years; 3 = 30–39 years; 4 = 40–59 years, 5 = 60–65 years) and gender (0 = male; 1 = female) because past studies have shown that age and gender affect MSCs in employees (Baur et al 2018 ; Elfering et al 2016 ). To take individual requirements into account, this study also controlled for full- or part-time employment, as suggested by Elfering et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Risk factors for neck pain include having a demanding job where people do not have much scope for activities [27]. A poor psychosocial work environment has been linked to musculoskeletal disorders [28,29] and is often related to time constraints [30].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship among stress, sleep problems, and musculoskeletal pain has been shown [30], but given the importance of sleep, it is strange how often lack of adequate sleep is omitted when assessing the general health of individuals-especially when assessing their musculoskeletal system [37]. High demands at work and a high workload are known to cause sleep disturbances [38,39], but stressful factors in the work environment are the most common causes of sleep problems [40].…”
Section: Introductionmentioning
confidence: 99%
“…The protective role of manual handling with loads for being on medication for MSD may well be due to “healthy worker effects” and uncontrolled confounding. Many authors believe that work strain mediates the association between work stressors and work-related musculoskeletal complaints, whereby the mental and physical mechanisms involved elicit muscle tension and induce musculoskeletal pain [ 25 ].…”
Section: Discussionmentioning
confidence: 99%